Awareness of employees’ interests as the interest of the enterprise. The case of PKP SA companies - Borowska, Magdalena (Znajomość interesów pracowników jako interes przedsiębiorstwa. Przypadek spółek PKP SA, 2019)
The aim of the article is to recognise the interests of employees in PKP SA companies and to determine the rank of these interests due to the motivational potential which lies in their implementation. This was conducted thorough studies of literature on the subject as well as empirical studies with the use of a questionnaire. Based on the review of the literature, the interests were divided into two groups: those protected by law and those that are partly or completely within the competence of the employer. Non-managerial staff (495 persons) were offered a second interest group for assessment. The motivational potential was determined by comparing the value that employees assign to particular interests with the perceived level of their implementation. High-value interests, whose degree of implementation the respondents rated the lowest were considered to be those with motivational potential; these are (in descending order): transparent rules of promotion, pay adequate to duties, equal treatment in employment, good working atmosphere, employment protection, safe working conditions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 145-154
Keywords: internal stakeholders; employees; employee interests; interesariusze wewnętrzni; pracobiorcy; interesy pracownicze